1996
DOI: 10.1073/pnas.93.3.1021
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes of tumor necrosis factor alpha associated with membrane insertion and channel formation.

Abstract: Low pH enhances tumor necrosis factor a (TNF)-induced cytolysis of cancer cells and TNF-membrane interactions that include binding, insertion, and ion-channel formation. We have also found that TNF increases Na+ influx in cells. Here, we examined the structural features of the TNF-membrane interaction pathway that lead to channel formation. Fluorometric studies link TNF's acid-enhanced membrane interactions to rapid but reversible acquisition of hydrophobic surface properties. Intramembranous photolabeling sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 34 publications
2
41
2
3
Order By: Relevance
“…In their study, Bruce et al (16) observed similar injury-induced increases in TNF protein in both wt and TNF receptor-deficient mice. The possibility exists that the prolonged presence of unbound TNF may induce pathologic cellular changes in a receptor-independent fashion (71,72). Alternatively, the differences between our observation and those of Bruce et al may be due, in part, to differences in the injury models, the time course of the pathological changes, and/or the strain of mice used.…”
Section: Discussioncontrasting
confidence: 53%
“…In their study, Bruce et al (16) observed similar injury-induced increases in TNF protein in both wt and TNF receptor-deficient mice. The possibility exists that the prolonged presence of unbound TNF may induce pathologic cellular changes in a receptor-independent fashion (71,72). Alternatively, the differences between our observation and those of Bruce et al may be due, in part, to differences in the injury models, the time course of the pathological changes, and/or the strain of mice used.…”
Section: Discussioncontrasting
confidence: 53%
“…TNF can, however, increase ALC in mice lacking both TNF receptors (24), strongly suggesting TNF receptor-independent actions of the cytokine. Moreover, TNF has a membrane insertion capacity (54). Also, intra-alveolar catabolism is an important mechanism of protein removal, which is particularly important during recovery from pulmonary edema (55).…”
Section: Discussionmentioning
confidence: 99%
“…However, interestingly, TNF␣ does regulate G proteins (55), and recently G proteins have been reported to regulate amiloride-sensitive sodium uptake in fetal alveolar type II epithelial cells (56). There is also recent evidence that TNF-␣ can increase uptake of sodium into cells by inserting an ion channel into cell membranes (57). In summary, acute P. aeruginosa pneumonia in rats results in a marked upregulation of the rate of net alveolar epithelial sodium and fluid clearance.…”
mentioning
confidence: 99%